Feminist Movement in 1884th in British Empire in Harry Bradbeer’s Enola Holmes (2020) - Silma Nadyan Nafis (Metaphor, 2021)
This study is aimed to analyze: (1) the social condition of women in Victorian era in Harry Bradbeer’s “Enola Holmes”. (2) The feminist movements reflected in Harry Bradbeer’s “Enola Holmes”. The study uses descriptive qualitative method to analyze the film entitle “Enola Holmes” directed by Harry Bradbeer as the objective of the research. The method of collecting data includes watching and reading, identifying, classifying, and selecting. The method of analyzing the data are displaying, explaining, and interpreting. The data analyzed by using Abnormal psychology and Sigmund Freud Psychoanalysis. The result of the study: (1) the social condition of women in Victorian era reflected in Harry Bradbeer’s Enola Holmes such as women are classified by social class, women are meant to be subordinate to men, women uneducated, women must be follow beauty standard in that era, women did not have a voting rights; (2) the feminist movement in Victorian era in form of movement in education, movement in politic life, and movement in liberty.